Bioanalytical Method Development and Validation of Antihelmintic Drug in Human Plasma - Sapna, Pandey A.; Jadhao, Monika P. (Asian Journal of Pharmaceutical Research and Development, 2024)
Triclabendazole is an anthelmintic or anti-worm medication. Asimple and sensitive bio-analytical HPLC method with UV detection was developed and validated triclabendazole in human plasma. The analytes were extracted from human plasma samples by liquid-liquid extraction technique. Triclabendazole showed maximum absorbance i.e.; λmax at 305 nm. The developed analytical method was validated as per ICH guidelines. The chromatographic separation was achieved with Hypersil BDS C18 (250 mm x 4.6 mm, Particle size: 5 µm), software Autochrom 3000 using a mobile phase composition of acetonitrile and buffer (60:40 V/V) at a flow rate of 1.2 mL/min with a run time of 7 min. The method showed good linearity in correlation coefficient (r) of >0.9998. The LOD and LOQ were found to be 1.00 µg mL-1 and 3.02 mg mL-1, respectively. Accuracy and precision data were found to be less than 2%, indicating the suitability of method. The developed HPLC method in human plasma using protein precipitation extraction for sample preparation was found to be very simple, reliable, precise, accurate, sensitive and selective analytical method for the estimation of Tricalbendazole. The method is suitable for routine quantitative analysis in pharmaceutical dosage forms. The method developed can be used in therapeutic drug monitoring units, bioequivalence and bioavailability studies, pharmacokinetic and toxicology studies of Tricalbendazole.